ANALISIS KEBIJAKAN : PROGRAM JAMINAN SOSIAL KESEHATAN SEMESTA SUMATERA SELATAN SEBAGAI IMPLEMENTASI URUSAN WAJIB PEMERINTAH DAERAH DI BIDANG KESEHATAN DALAM KERANGKA OTONOMI DAERAH DI KABUPATEN OKI - Retnaningsih, Ekowati (Publikasi Penelitian Terapan dan Kebijakan, 2009)
Indonesia has low number 40/2004 about National Social Security System that is all of Indonesia people must have health insurance. Low number 32/2004 about autonomy to instruct that province and district region have obligation to improve health status all of our people. South Sumatra Province Government with District Government launching Social Health Insurance Program start 22 January 2009. The means this research are to know existing condition of input aspect, process aspect and output aspect with all of problem in Ogan Komering Ilir (OKI) District. This research use policy analysis design with approach mix paradigms are quantitative and qualitative design. Quantitative research get secondary data and qualitative research get primer data. It uses 24 people informant representative. Collecting of quantitative data uses in-depth interview and focus group discussion method. Validation of data use source triangulation and method triangulation. Research results were: 1) The out patient utilization was 118.346 visitor (30,6%) in part were 3.394 visitor (2,87%) are pay. 2) The in patient was 4.620 visitor (1,2%) in part were 1.317 visitor (28,5%) are pay. 3) The room of secretariat is too small, without airship wardrobe and computer. 4) They have not budget for operational and secretariat budget. 5) Verification of member need long time because have not the member database. 6) Visiting hours was not enough.